Evaluation of disturbance torques exerting on mobile manipulators traveling on irregular terrain - Hatano, M.; Ohsumi, T.; Obara, H. (2003 IEEE/ASME International Conference on Advanced Intelligent Mechatronics : proceedings : (AIM 2003) : July 20-July 24, 2003, International Conference Center, Port Island, Kobe, Japan, 2003)
In the present research, we evaluate disturbance torques derived by terrain during traveling on irregular terrain quantitatively based on the proposed model of a dynamic mobile manipulator. Terrain irregularities exist even in structures such as the man-made floors of factories and buildings. When a mobile manipulator's hand is required to operate precisely while traveling on irregular terrain, it is subject to disturbance torques caused by traveling across such terrain. Therefore, a compensation method of decreasing control errors caused by disturbances due to terrain must be considered. In this paper, disturbance torques caused by irregular terrain are defined based on our proposed model. Relationships between changes in disturbance torques, changes in periods of terrain and changes in traveling speed are evaluated quantitatively by simulations.